Clinical Study of Gynecological Problems in Adolescent Age Group at Tertiary Care Center - Dr. karalla chandana; Dr. Anita pawa; Dr.B.B.Yadav, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: According to WHO adolescence is the age between 10-19 years Adolescents constitute 21.4% of the population in India [1]. It is the period where enormous physical and psychological changes occur. Hormonal events play a key role in this transition. Profound bodily changes, sexual development and altered emotional and behavioural changes are observed during this period, besides endocrine influences, genetic, nutritional and other environmental factors play an important role during this transitional period of life. Aim and Objectives: 1. Clinical study of gynaecological problems in adolescent age group at tertiary care center. 2. To study proportion of different gynaecological problems in adolescent girls.3.To study the etiological factors in different gynaecological problems in adolescent girls.4.To study the treatment modalities in different gynaecological problems in adolescent girls. Methods: Study Design: Cross sectional study. Study place: OBGY Department of VDGMC Latur, Maharashtra, India. Study Duration: September 2022 to May 2024. Study population: The study was conducted on all adolescent girls who were from urban and rural surroundings of tertiary care center visited the gynecology OPD. Study sample: 180 ResuResult: Majority of gynecological problems are present in late adolescent age group. In 180 cases admitted cases are 12 cases [6.66%] and 168 cases [93.3%] are from OPD. 26 cases who has normal menstrual patterns presented with dysmenorrhea (14 cases) and 8 cases with leucorrhea and 3 cases with dysuria and 1 case with mass per abdomen. most of the cases presented with hirsutism and acne 40 cases (22.22%) followed by Leucorrhoea and itching 29 cases (16.11%), Teenage pregnancy found in 12 cases (6.66%), overweight 6 cases(3.33%), Mass per abdomen 6 cases(3.33%), dysuria 3 cases (1.66%), Precocious puberty 1 case (0.55%) and Delayed puberty 1 case (0.55%). most common etiopathology was AUB 96 cases (53.33%) followed by PCOS 39 cases (21.66%) and 4 cases diagnosed with Mullerian agnesis (2.22%),14 cases (7.77%)thyroid disorders, 06 cases(3.33%) hyperprolactinemia, 10 cases with vaginal infections and 02 cases with urinary tract infections. most common treatment modalities was Hormonal treatment 56 cases (31.11%) followed by Iron tablets in 59cases (32.77%), Blood transfusions in 2 cases(1.11%),Tranexamic acid in 38cases (21.11%), Mefenamic acid in 32 cases(17.77%),Thyroxin in 14cases[7.77%],Surgery in 10 cases (5.55%),Cabergoline in 4 cases[2.22%],antifungal in 4 cases (2.22%) , Antibiotics in 6 cases[5.55%], AKT in 1 case(0.55%). Many girls treated with multiple modalities. Conclusions: Dysmenorrhea and heavy menstrual bleeding as predominant symptoms and excessive weight gain is most common examination finding. Majority of cases treated with hormonal treatment and iron supplementation.